2021
DOI: 10.3390/healthcare9111472
|View full text |Cite
|
Sign up to set email alerts
|

Is the Pain Just Physical? The Role of Psychological Distress, Quality of Life, and Autistic Traits in Ehlers–Danlos Syndrome, an Internet-Based Survey in Italy

Abstract: Background: Ehlers–Danlos syndromes (EDS) have been associated with psychological distress, comorbid psychiatric disorders, and worsening in quality of life (QoL). Among the neurodevelopmental disorders, autism spectrum disorders (ASD) have shown the highest rates of co-occurrence with EDS. The reasons for these associations are unknown and a possible role of pain in increasing the risk of psychiatric disorders in EDS has been suggested. However, a detailed picture of an Italian EDS sample is still lacking. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These medications also have vasoactive properties, effects on autonomic function and a range of gastrointestinal side effects 4,65,74 Mental health contributors : There is a recognized increased prevalence of mental health disorders in patients with HSD/hEDS, including anxiety and depression 38,75–77 . In a retrospective survey of 391 patients with a diagnosis of mostly HSD (80%) or EDS (notably no hEDS), almost half of the respondents were affected by a psychiatric disorder and almost 30% described two or more simultaneous psychiatric diagnoses 75 .…”
Section: Pathophysiological Contributors To Gastrointestinal Symptoms...mentioning
confidence: 99%
See 1 more Smart Citation
“…These medications also have vasoactive properties, effects on autonomic function and a range of gastrointestinal side effects 4,65,74 Mental health contributors : There is a recognized increased prevalence of mental health disorders in patients with HSD/hEDS, including anxiety and depression 38,75–77 . In a retrospective survey of 391 patients with a diagnosis of mostly HSD (80%) or EDS (notably no hEDS), almost half of the respondents were affected by a psychiatric disorder and almost 30% described two or more simultaneous psychiatric diagnoses 75 .…”
Section: Pathophysiological Contributors To Gastrointestinal Symptoms...mentioning
confidence: 99%
“…4,65,74 • Mental health contributors: There is a recognized increased prevalence of mental health disorders in patients with HSD/hEDS, including anxiety and depression. 38,[75][76][77] In a retrospective survey of 391 patients with a diagnosis of mostly HSD (80%) or EDS (notably no hEDS), almost half of the respondents were affected by a psychiatric disorder and almost 30% described two or more simultaneous psychiatric diagnoses. 75 Significant associations were noted between gastrointestinal dysfunction and mood disorders (OR 2.07, 95% CI 1.33-3.…”
Section: • Dolichocolon (Elongation or Redundancy Of The Colon)mentioning
confidence: 99%
“…Older patients and patients who are diagnosed later in life reported less availability of support from friends and family and were also more likely to have a psychological disorder. Previous literature has shown that the consequences of delayed diagnosis can include poorer health‐related quality of life and increased psychological issues (Kalisch et al, 2020; Rocchetti et al, 2021). It is possible that patients diagnosed at older ages have a more prolonged diagnostic odyssey, which can lead to unaddressed medical needs that exacerbate some symptoms of hEDS.…”
Section: Discussionmentioning
confidence: 99%
“…The most common subtypes of EDS are classical, classical-like, hypermobile, cardio-valvular, and vascular creating a prevalence of one in 5,000 people worldwide [ 1 , 2 , 3 , 4 , 5 , 6 ]. Treatment for EDS is often limited to supportive measures with medications targeting pain, anti-inflammatory, and cardiovascular symptoms, as well as complications [ 7 , 8 , 9 , 10 ]. Osteopathic manipulative treatment (OMT) is a potential alternative in symptomatic relief for EDS patients; however, only a few case reports have documented OMT use in this population.…”
Section: Introductionmentioning
confidence: 99%